Experimental investigation of pretensioned bolts under cyclic loading: Damage assessment using acoustic emission - Tieliang An; Xigui Zheng; Dengxing Zhu; Deyu Qian; Yu Guo; Juncai Cao (International Journal of Distributed Sensor Networks)
Understanding the acoustic emission effects on bolts under cyclic loading is of great significance for the support of roadways. The presented research focuses on the acoustic emission characteristics of bolts under cyclic loading. The following main conclusions were drawn: (1) With a higher loading frequency, the acoustic emission counts rate increases, while the total energy released in a given cyclic loading path decreases. (2) A fitting formula is established according to the relationship between the tension amplitude and cumulative acoustic emission counts, which can analyze the tension magnitude level of the cyclic load. (3) A damage factor for a cyclic load is proposed based on the acoustic emission counts generated during the cyclic and monotonic loading process that can analyze the degree of damage to the anchorage system caused by the cyclic load. (4) Based on the spatial distribution of the acoustic emission orientation points and the acoustic emission energy generated during the pull-out process, the acoustic emission damage evolution process of the anchorage specimens is deduced, and the mechanism of the high stability of the pretension anchorage system after cyclic loading is analyzed. The above conclusions may provide some experimental references for the application of acoustic emission technology in bolts supporting roadways.